Is Western European Agriculture Resilient to High Temperatures? - Emanuele Massetti; Steven Van Passel; Camila Apablaza (Center for Economic Studies and ifo Institute (CESifo), 2018)
We estimate a Ricardian model of Western European agricultural land values using farm-level data. We model the effect of temperature on land values using a flexible specification of daily mean temperature to test if there are temperature threshold effects. Results indicate that there are no temperature thresholds beyond which agricultural land values suddenly drop. The results are robust to alternative model specifications. Adaptation explains why a smooth aggregate response function is compatible with sharply non-linear crop yield functions. With adaptation, the effect of warming on Western European agriculture is likely to be smooth.
Keywords: Q12; Q21; Q51; Q54; 330; agriculture; climate change; extreme temperature; Ricardian; threshold; Europe